FAKTOR LINGKUNGAN FISIK YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA DI KABUPATEN PELALAWAN - Harnani, Yessi; Yulviana, Rina (Ensiklopedia of Journal, 2021)
Pneumonia is a disease that attacks the lungs and is characterized by coughing and difficulty breathing. The prevalence of pneumonia in children under five in Indonesia in 2017 was 46.34% and the number of under-five deaths due to pneumonia/Case Fatality Rate (CFR) was 0.3%. Pneumonia cases in toddlers in Pelalawan Regency are quite high, namely in 2018 there were 72% of cases. The purpose of this study was to determine the physical environmental factors associated with the incidence of pneumonia in children under five in Pelalawan District, Riau Province. This type of quantitative analytic research with cross sectional design. The number of samples is 400 households with toddlers using cluster sampling technique. Data analysis was univariate, bivariate and multivariate with multiple logistic regression. The results showed that there was a relationship between the type of house walls (P value: 0.000; POR: 11.23), humidity (P value: 0.001; POR: 5.09), residential density (P value: 0.003; POR: 3.51), and lighting (P value: 0.000; POR: 5.14), with the incidence of pneumonia in children under five. Variables that are not related to the incidence of pneumonia in children under five are the type of floor and ventilation. In conclusion, the type of wall of the house that does not meet the requirements has a risk of 11.2 times for the occurrence of pneumonia in children under five compared to the type of wall of the house that meets the health requirements. It is hoped that the health office will increase the socialization of healthy homes that meet health standards.